Numerical Investigation of Oil–Water Exchange Behaviors in Shale During Post-Fracturing Soaking Periods - Wang, Fei; Chen, Qiaoyun; Zhang, Jingchen; Ruan, Yingqi; Zhuang, Ye; Zhu, Jian; Zhang, Shicheng (Frontiers in Earth Science, 2021)
Fracturing-fluid imbibition and retention are treated as a main mechanism for oil production from shale reservoirs. However, the oil-water exchange phenomenon during post-fracturing soaking periods has not been thoroughly studied. In this study, a water-oil flow model is built to investigate the water imbibition and oil drainage phenomenon in hydraulically fractured shale. With the developed numerical simulator, the main characteristics of post-fracturing soaking, i.e. pressure diffusion, water imbibition and especially the oil-water exchange behaviour are simulated. Three key time points, i.e. oil-water exchange equilibrium, steady exchange efficiency and oil breakthrough in fracture are found. The oil-water exchange efficiency and exchange volume are also calculated. Moreover, the proposed model is validated by field wellhead pressure dynamics, indicating a relevance of time between the oil-water exchange efficiency and the wellhead pressure falloff derivatives. Finally, the influences of shale permeability, wettability, fracture complexity and oil viscosity on the oil-water exchange behavior are investigated. Results indicate that the matrix of oil-wet shale almost does not suck water and discharge oil, and only the oil in natural fractures exchanges with the water in hydraulic fractures. The water-wet shale with low permeability, high oil viscosity, and few natural fractures needs extra soaking time to achieve good oil-water exchange performance. The suitable soaking period for the water-wet base case in this study is from 17.25 to 169 days, among which 64 days is the optimal soaking time.